Pomah as a housing well being model in region of Yogyakarta Rent Flats - Rahmawati, Intan; Koentjoro, Koentjoro; Ikaputra, Ikaputra (Jurnal Psikologi Sosial, 2024)
Rapid urban growth often causes housing problems resulting from diminishing settlement areas. Rent flats is therefore considered to be the solution for utilizing small spaces. This research investigates how dynamic psychological prosperities affect residents of average-rent flats. Specifically, this research aims to achieve housing well-being by identifying the primary needs of housing well-being to encounter prosperous psychological problems. The present research is conducted in Region of Yogyakarta rent flats, Rusunawa Dabag and employed an action research approach to resolve the main questions answered by six steps. They are the entrance, taking diagnosis, action planning, action taking, evaluation, and reflection. The result of the data analysis finds that the problems of social control and a sense of community in interacting dynamically between individuals and their residences implicate cognitive, affective, and attitude processes. Based on the process and the result of the research, prompts are needed to achieve a harmonic situation to live in a vertical residence for aspirant residents, representative residents as a community, and administrators. The prompts are in the form of training aimed at developing preparation in understanding changes in living habits from landed houses to vertical flats for new residents. Furthermore, this research also revealed that the tenants of Dabag Rusunawa apply guyub (alliance), rukun (cordiality), and, tertib (orderly) as the main indicators in providing a sense of Pomah (a sense of comfort and prosperity at home).